Bisnis Online Agent Ilegal dalam Perkembangan Industri Pariwisata Bali - I Gusti Ayu Putu Widia Wijayanti (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2017)
The increasing number of illegal online travel agencies recently has become a hot issue that being discussed by the entrepreneurs of tourism business service in Bali. This kind of business has triggered tariff competition, which is unhealthy and has negative impact on the existence of travel agency business in Bali. Therefore, this phenomenon becomes an interesting issue to be investigated. Aims of the investigation were to know the growth of illegal online travel agent business, its impacts and to formulate policies for controlling it that are more relevant to present condition, creating conducive, harmonious, and balanced tourism business in Bali. The impactsof illegal online travel agents were classified into economic, social, culture, and impacts on images. Dealing with illegal online travel agent business, it was observed that there was no negative impacts of tourist. The tourist stated that they were remain satisfied to the services given by illegal online travel agents. The effort made by the governments was still limited on providing suggestion, because there has not been a strong punishment for the offender. Thus, it is recommended that there is a need to set up a policy to control illegal online travel agent in Bali. The local government should formulate more effective and efficient policies, to restore theharmony and balanced conditions of tourism business in Bali. In addition, for the travel agency management, they should obey the law and regulations in running the business.